(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
Andrew Murray frankly admits that he owed much to William Law. Speaking of Law, he says: “I confess that in all my reading I have never found anyone who has so helped me in understanding the Scripture truth of the work of the Holy Spirit.” In Law he discovered a rich store of ideas and in four books he gave extracts from Law’s works: Wholly for God, The Divine Indwelling, The Spirit of Love, and Dying to Self. Law’s mysticism was not original in a strict sense, but the English interpretations of the works of the German mystic, Jacob Boehme, by Dionysius Andreas Freher. Also the Platonist influence of Anglican mysticism provided a platform for Law’s mystical inclinations. The upshot of these influences on Law’s spirituality was a mysticism with strong undercurrents of Neo-Platonic mystical spirituality. Law’s mystical conceptualisation of the soul, desire, the human will, humility, the love of God, and the mystical unification of the human soul with God, contributed largely to Murray’s theological views on the universal revelation of love, atonement and the meaning of Christ’s suffering. At the centre of Murray’s mystical spirituality is the Boehme-Law idea of the great mystery of man’s creation with a free will, the renewal of his will in redemption, and that God has made the execution of His will, in many things, dependent on the will of man.